Information retrieval and scientific visibility from the perspective of persistent identifiers - Santos, Thamyres Vieira dos (2023)
Discusses the use of persistent allotal and institutional identifiers in the organization and access to scientific information in a digital environment, aiming to verify such forms of informational representation to optimize retrieval. The research is of a bibliographic and documentary nature, counting on a bibliographic survey for the theoretical basis of the arguments; and it is also practical in that it analyzes the applicability of two persistent organizational identifiers and three persistent authorial identifiers, through experimental verification in recovery platforms. As a result, the analysis of the use of persistent identifiers shows that the initiatives are not yet widely adopted and most sources do not present search options for these fields. It is concluded that it is essential to carry out research that discusses the use of persistent identifiers and evidence the need to strengthen unique initiatives, whether authorial or organizational, providing a broad understanding and use by researchers and institutions, consolidating itself as facilitators in accessing scientific information, especially in a digital environment.